Envelope for autograph letter from Myra Hess - Hess, Myra, 1890-1965:::Creator::::::::::::; Isaacs, Harry, 1902-1972:::Contributor:::::::::::: (United Kingdom; London, 2021)
Envelope for an autograph letter signed from Myra Hess to the pianist Harry Isaacs, from London, postmarked October 8, 1932